Uji Efektivitas Ekstrak Daun Kumis Kucing (Orthosiphon stamineus) Terhadap Pertumbuhan Bakteri Staphylococus epidermidis - Kristin Natalia Makatita Makatita; Erni Yohani Mahtuti; Faisal (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Staphylococcus epidermidis is a bacteria that causes diseases such as urinary tract infections, kidney infections and mostly causes swelling (abscesses) such as acne and skin infections. This bacteria is one of the most common species of the genus Staphylococcus bacteria in clinical interest. Cat's whiskers (Orthosiphon stamineus) is a herbal plant, Lamiaceae family which is used as an antioxidant and is able to inhibit bacteria because it contains antibacterial compounds, namely flavonoids, tannins, triterpenoids and saponins. The purpose of this study was to determine the effect of cat's whiskers leaf extract in inhibiting the growth of S.epidermidis. Experimental research type. Disc diffusion method, paper disk planting technique. The results of the study on the inhibition zone A1 (cat's whiskers leaf extract concentration 25%) 7mm, A2 (cat's whiskers leaf extract concentration 50%) 8.375, A3 (cat's whiskers leaf extract concentration 75%) 12.6 mm are categorized as resistant, and A4 (cat's whiskers leaf extract concentration 100%) 15.258 mm are categorized as intermediate, which shows that A4 is the most sensitive and has the most even distribution in inhibiting the growth of S. epidermidis. The results of One Way Anova have a sig value <0.05 there is a significant difference in the four extracts and their positive controls meaning that there is an effect of the concentration of cat's whiskers leaf extract on the growth of S. epidermidis. The conclusion of this study is that there is an effect of the concentration of cat's whiskers leaf extract on the growth of Staphylococcus epidermidis.